Biohydrogen from dilute side streams - Influence of reaction conditions on the conversion and selectivity in aqueous phase reforming of xylitol. (July 2020) - Aho, Atte; Rosales, Carlos; Eränen, Kari; Salmi, Tapio; Murzin, Dmitry Yu.; Grénman, Henrik
Abstract: Aqueous phase reforming (APR) can be used as an efficient method to purify and obtain added value from rather dilute side/waste streams of process waters containing e.g. alcohols or sugar alcohols. Such side streams often have none or even negative value due to purification costs, which contributes to the economy of the process. Xylitol was here used as a model compound. The desired product in the current study was hydrogen, which can be used for valorizing by-products via hydroprocessing or as a bioenergy source. In addition to hydrogen, some alkanes were also obtained, which are prime sources of bio-energy for power production. The current work focused especially on the influence of the reaction conditions (temperature, pressure and inert gas flow) on the xylitol conversion and hydrogen selectivity, which has not been reported previously. The influence of reaction conditions on the aqueous phase reforming of xylitol on Pt/Al2 O3 catalyst was studied in a trickle-bed reactor. Selectivity to hydrogen was dependent on gas flow through the reactor, especially the absence of any gas resulted in a low selectivity. A higher reaction temperature and a higher inert gas flow gave a better xylitol conversion, while an increase of the overall pressure had an opposite effect on conversion. The activation energy for xylitol conversion was determined for the first time being 79.3 kJ/mol. The results demonstrate that aqueous phase reforming is a viable method for energy efficient value added processing of sugar alcohol containing dilute side streams in modern bio-refinery applications. Highlights: Biohydrogen and some alkanes were obtained for use in biofuels, biochemicals and bioenergy production. Practically full conversion was achieved in a trickle bed reactor system. The liquid-to-gas ratio and operating pressure influenced significantly the conversion and to some extent also selectivity. Temperature influenced the conversion significantly, however, the influence on selectivity was not very significant. The activation energy for xylitol conversion was determined for the first time being 79.3 kJ/mol.